Manajemen Program Tahfidz Al-Qur'an dalam Meningkatkan Mutu Pendidikan di SD Qurrota 'Ayun Kalibeber Wonosobo - Tri Dewi Fatimah; Nasokah Nasokah; Ali Mu`tafi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to describe the management of the Tahfidz Al-Qur'an Program, identify the supporting and inhibiting factors in its implementation, and analyze its contribution to improving educational quality at SD Qurrota 'Ayun Kalibeber Wonosobo. A qualitative approach with a field research design was employed. Data were collected through observations, interviews, and documentation involving the principal, tahfidz coordinator, tahfidz teachers, classroom teachers, students, and parents. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings show that the Tahfidz Al-Qur'an Program has been systematically managed through the functions of planning, organizing, actuating, and controlling. Planning includes determining memorization targets, preparing the curriculum, scheduling activities, selecting learning methods, assigning qualified teachers, and establishing evaluation procedures. Organizing involves a clear distribution of responsibilities among school stakeholders and parents. Program implementation consists of tahsin, memorization submission, muraja'ah, and periodic evaluations, while monitoring is conducted through memorization assessments, evaluation meetings, and progress reports to parents. Supporting factors include the principal’s commitment, competent tahfidz teachers, parental involvement, and a religious school environment. Inhibiting factors include differences in students’ abilities, limited muraja'ah at home, time constraints, and fluctuating learning motivation. The program contributes to educational quality by strengthening religious character, improving academic achievement, fostering school discipline, and increasing public trust in the institution.